Structure-guided combination therapy to potently improve the function of mutant CFTRs. (November 2018) - Veit, Guido; Xu, Haijin; Dreano, Elise; Avramescu, Radu; Bagdany, Miklos; Beitel, Lenore; Roldan, Ariel; Hancock, Mark; Lay, Cecilia; Li, Wei; Morin, Katelin; Gao, Sandra; et al.
Abstract Available corrector drugs are unable to effectively rescue the folding defects of CFTR-ΔF508 (or CFTR-F508del﻿), the most common disease-causing mutation of the cystic fibrosis transmembrane conductance regulator, a plasma membrane (PM) anion channel, and thus to substantially ameliorate clinical phenotypes of cystic fibrosis (CF). To overcome the corrector efficacy ceiling, here we show that compounds targeting distinct structural defects of CFTR can synergistically rescue mutant expression and function at the PM. High-throughput cell-based screens and mechanistic analysis identified three small-molecule series that target defects at nucleotide-binding domain (NBD1), NBD2 and their membrane-spanning domain (MSD) interfaces. Although individually these compounds marginally improve ΔF508-CFTR folding efficiency, function and stability, their combinations lead to 50–100% of wild-type-level correction in immortalized and primary human airway epithelia and in mouse nasal epithelia. Likewise, corrector combinations were effective against rare missense mutations in various CFTR domains, probably acting via structural allostery, suggesting a mechanistic framework for their broad application. Targeting different aspects of mutant CFTR structural defects with combination therapy leads to more potent rescue of function than that following single therapy.